Association of Life's Simple 7 and ideal cardiovascular health in American Indians/Alaska Natives. Issue 1 (6th April 2023) - Rawal, Smita; Johnson, Blake Ryan; Young, Henry Nolan; Gaye, Bamba; Sattler, Elisabeth Lilian Pia
Abstract : Objective: American Indians and Alaska Natives (AI/ANs) are an understudied population at high risk for cardiovascular diseases (CVDs); little is known about contextual factors contributing to CVDs in AI/ANs. This study examined the association of Life's Simple 7 (LS7) factors and social determinants of health (SDH) with CVD outcomes in a nationally representative sample of AI/ANs. Methods: We conducted a cross-sectional study of 8497 AI/ANs using 2017 Behavioural Risk Factor Surveillance Survey data. Individual LS7 factors were summarised as ideal and poor levels. Coronary heart disease, myocardial infarction and stroke were defined as CVD outcomes. Healthcare access measures represented SDH. Logistic regression analyses examined associations of LS7 factors and SDH with CVD outcomes. Population attributable fractions (PAFs) quantified individual contributions of LS7 factors to CVD outcomes. Results: N=1, 297 (15%) participants with CVD outcomes were identified. Smoking, physical inactivity, diabetes, hypertension and hyperlipidaemia were LS7 factors associated with CVD outcomes. Hypertension was the largest contributor to CVD (aPAF 42%; 95% CI 37% to 51%), followed by hyperlipidaemia (aPAF 27%; 95% CI 17% to 36%) and diabetes (aPAF 18%; 95% CI 7% to 23%). Compared with individuals with poor LS7 levels, participants with ideal levels showed 80% lower odds of CVD outcomes (aOR 0.20; 95% CI 0.16 to 0.25). Access to health insurance (aOR 1.43, 95% CI 1.08 to 1.89) and a regular care provider (aOR 1.47, 95% CI 1.24 to 1.76) were associated with CVD outcomes. Conclusions: Effective interventions are needed to address SDH and attain ideal LS7 factors to improve cardiovascular health among AI/ANs.